PATH-14. GENETIC SUSCEPTIBILITY AND OUTCOMES OF PEDIATRIC, ADOLESCENT AND YOUNG ADULT IDH-MUTANT ASTROCYTOMAS. (4th December 2020) - Bornhorst, Miriam; Nobre, Liana; Zapotocky, Michal; Barseghyan, Hayk; Goecks, Jeremy; Boue, Daniel; Tabori, Uri; Hawkins, Cynthia; Bouffet, Eric; MacDonald, Tobey; Schniederjan, Matthew; Bronischer, Alberto; et al.
Abstract: INTRODUCTION: Previously thought to be rare, recent case series have shown that IDH mutations in young patients are more common than previously described. In this study, we analyzed IDH -mutant tumors to determine clinical significance of these mutations in children, adolescents and young adults. METHODS: Through this multi-institution study (10 institutions), we collected 64 IDH1/2-mutant infiltrating astrocytoma specimens from 58 patients aged 4–26 (M:F, 0.4:0.6). Specimens included 46 low-grade (LGG) and 18 high-grade (HGG) astrocytomas. Tumor sequencing data (n=45), germline sequencing data (n=37) and outcome data (n=40) was analyzed. RESULTS: Similar to adults, most sequenced tumors had a co-mutation in the TP53 gene, while ATRX mutations were less common and primarily seen in HGGs. Approximately 60% (n=21) of patients with germline data available had a mutation in a cancer predisposition gene. Mismatch repair (MMR) mutations were most common (n=12; MSH6 n=9), followed by TP53 mutations (n=7). All patients with MMR gene mutations had HGGs and poor progression free (PFS=10% at 2 years, mean TTP=9 months) and overall (OS <30% at 2 years) survival. Despite an OS of 90% at 5 years, many LGG patients had tumor progression/recurrence requiring additional treatment (PFS= 80% at 2 yrs, 40% at 5 yrs, mean TTP=3.5 years). Four LGG tumors (2 with TP53+ATRX loss, 2 with TP53 loss+1p19q co-deletion) underwent malignant transformation. CONCLUSION: IDH -mutant tumors in pediatric patients are strongly associated with cancer predisposition and increased risk for progression/recurrence or malignant transformation. Routine screening for IDH1/2 mutations in children with grade 2–4 astrocytomas could greatly impact patient management.